Growth performance of calves fed shoti, wheat and soybean based milk replacers (Bangladesh Journal of Livestock Research, 2016)
A study was conducted with objectives to determine the comparative growth performance of calves fed shoti, wheat and soybean based milk replacers and their economics. To achieve the objectives, a total of 24 local calves of about 6-10 days of age were selected and divided in four groups; having six (6) calves in each. A limited suckling with feeding whole milk considered as control (To), suckling along with feeding of wheat, shoti and soybean based milk replacer considered as treatments and denoted as T1, T2 and T3, respectively. Results obtained in the present study revealed that, the total DM, OM and CP intake did not differ significantly (p>0.05) among the treatment groups. However, calves in T2 group sucked significantly (p0.05) was observed in average daily weight gain (ADG) of calves among the treatment groups. The feed conversion efficiency (FCR) was relatively better (p>0.05) in calves those fed shoti and soybean based MR compared to calves fed wheat and control diets. The overall levels of both glucose and BUN did not differ significantly (p>0.05) in calves under different treatment groups. The total cost of per kg wheat (T1), shoti (T2) and Soybean (T3) based MR were Tk. 52.69, Tk. 94.45 and Tk. 51.11, respectively. The processing cost per kg MR was increased Tk. 41.00-43.00 in T2 group than that of T1 and T3 groups. The feeding cost per calf per day was reduced Tk. 88.93.00 Tk. 57.87 and Tk. 82.55 in T1, T2 and T3, respectively than that of T0 group. Results considering for both FCR and per day feeding cost, it indicates that T2 and T3 diets i.e, shoti and soybean based MR maintained growth of calves compared to wheat based MR and milk fed calves.Bangladesh J. of Livestock Res. 19(1-2): 33-43, Jan-Dec 2012